(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe epidemiological characteristics, methods of care, the level of physical development of children under 6 months of age to come to the National Children Hospital clinic in 2020. Subject: Mothers and children <6 months old to the first visit at National Children Hospital from January 2020 to December 2020. Research methodology: Cross-sectional description. Results and conclusions: 18.7% of infants were exclusively breastfed for the first 6 months, 45.6% of infants were given early solids. 48.6% of children use formula milk because mothers did not have enough milk, 30.6% because mothers had to go to work early. 98.9% of mothers and grandmothers prepare baby food, however 58.3% did not follow the proper methods. 52.9% of babies were breastfed <1 hour after delivery, 41.0% of mothers knew how to breastfeed properly.